MATERIALS FOR CEMENTING THE SURFACES OF DETAILS AND THEIR STANDARDIZATION - Tashkoziyeva, Zulfiya Eraliyevna (Educational Research in Universal Sciences, 2023)
Heating occurs during heat treatment of steels Chemical-thermal treatment changes its hardness technological that occurs in the production process by increasing elimination of defects, defects.